The Union of Soviet Architects of the USSR: The History of Its Formation and Early Stages (1932-1940s) - Meerovich, Mark (project baikal, 2015)
The article describes the history of the formation of the «Union of Soviet architects of the USSR» from 1932 to 1941. It presents the decisions of the highest bodies of the party-state apparatus to create the Union of Architects. It also describes the reasons for the ban on creative organizations of architects, artists, writers, composers, and so on. The article discloses the relationship between the power policy and the fulfillment of its decisions by Soviet intellectuals. The functions of the «authorized» Union of Architects and its role in subordination of Soviet architects to the policy implemented by the authorities are also described here.